Asian Ethnology Update - Dorman, Benjamin (Bulletin of the Nanzan Institute for Religion & Culture, 2011)
The first report on Asian Ethnology was published in the Bulletin of the Nanzan Institute for Religion and Culture 32 (2008, pp. 28–30). This update discusses the progress and developments related to the journal over the past three years, and to raise issues related to the journal’s future.